Bettering humanomics a new, and old, approach to economic science - McCloskey, Deirdre N. (University of Chicago Press, 2021)
"In Bettering Humanomics: A New and Old Approach to Economic Science, Deirdre Nansen McCloskey offers a critique of contemporary economics and a proposal for a better humanomics. McCloskey argues for an economic science that accepts the models and mathematics, the statistics and experiments of the current orthodoxy, but also attests to the immense amount we can still learn about human nature and the economy. From observing human actions in social contexts, to the various understandings attained by studying history, philosophy, and literature, McCloskey presents the myriad ways in which we think about life and how we justify and understand our actions in a synergistically human approach towards economic theory and practice"--